VERBAL I NON-VERBAL METHODS TEACHING THE DISCIPLINE "DECORATIVE-PH PHASE ART" (Pedagogy of Higher and Secondary Education, 2022)
The question of choice of methods of teaching for the high-quality mastering of theoretical knowledge’s, acquisition of practical abilities and skills is explored by the students of educational establishments of artistically-pedagogical education on a course "Decoratively-applied art”.
Keywords: perception; thought; capacity for teaching; verbal and unerbal methods of teaching; quality of mastering of knowledge’s